Haematological Study in Response to Varying Doses of Estrogen in Broiler Chicken - Khan, Taseer Ahmed; Zafar, Farhat (International Journal of Poultry Science, 2005)
Present study was conducted at the Poultry Physiology Unit, Department of Physiology, University of Karachi. Study evaluated the response of varying Estradiol valerate (a synthetic estrogen) doses in broilers (chickens) on the RBC, ESR and Hb at different ages. Two trials were carried out on 100-day-old broiler chicks. Estrogen was injected in volumes of 1ml, 3ml and 5ml subcutaneously in neck. Birds were bled at every 6-hour for 24 hours. A highly significant difference was noted among the control and treated birds for the parameters evaluated. A decrease in RBC and Hb values with an increase in the ESR was observed. Increasing the dose produced more significant results. Statistical comparison between the control and treated birds was found significant (P < 0.05) whereas a non-significant difference was obtained upon comparison between ages i.e. 40 and 50 days for RBC, ESR and Hb values.